The Effect of Ozone Treatment on the Quality of Biodiesel from Waste Cooking Oil - Setyawati, Sri Redjeki; Wibowo, Singgih (Makara Journal of Science, 2025)
This research demonstrates the successful production of biodiesel from waste cooking oil (WCO) using the transesterification method. A methoxide solution, formed by employing a base catalyst and alcohol, facilitated the conversion of triglycerides into methyl esters and glycerol as the byproduct. The conversion process yielded 74% biodiesel and 13.5% glycerol content, with the remaining proportion consisting of water and contaminants. The application of ozone (O3) aeration proved effective in reducing contaminants—such as alcohol, unreacted catalysts, food residues and water—by approximately 60%. Furthermore, Fourier transform infrared (FTIR) testing affirmed that the biodiesel product—treated with O3 aeration—maintained its original characteristics, thus ensuring the product’s quality. In conclusion, this study highlights the potential of biodiesel production from WCO and emphasizes the importance of O3 aeration in enhancing product purity. This finding is crucial for scaling up the biodiesel production process for broader industrial applications.